Sistema de Avaliação de Reabilitação e Comparativo de Custos (SARC): edifícios verticais de concreto armado para uso habitacional em centros urbanos do Brasil - Silva, Luiz Gustavo Zuliani da (Universidade do Vale do Rio dos Sinos, 2022)
Given many abandoned, unfinished and uninhabited buildings in urban centers, the rehabilitation of buildings is an area that can be further explored by civil construction in Brazil. This study seeks to address solutions implemented in other countries, focusing on methods used to assess the state of these buildings with a view to rehabilitation. It aims to develop a rehabilitation evaluation system and comparative unit costs of vertical buildings with reinforced concrete structures compared to the cost of new construction. The research comprehends four cycles. In Cycle 1, subsystems and functional elements were determined, criteria were defined to assess the level of rehabilitation and cost weighting. In Cycle 2, cost estimates for rehabilitation and new works were chosen based on the compilation of data on the costs of rehabilitated works and new works in the Brazilian context. Cycle 3 presents the structuring of the system and, finally, Cycle 4 demonstrates the application of the pilot test. The validation of the system took place with the application of a pilot project in five selected buildings in the cities of Rio Grande do Sul and São Paulo. The system is structured in 4 modules and includes the evaluation of 21 functional elements by visual inspection and calculates a rehabilitation index that defines the level of rehabilitation of the building. The results are presented in cost estimates, comparing the cost of rehabilitation with the cost of new construction within a range (optimistic, realistic and pessimistic). The application of the system in the pilot project showed that the results are consistent, close to the results obtained in the rehabilitation of the five buildings studied.
Keywords: Sistema de avaliação; Reabilitação; Custos unitários; Centros urbanos; Evaluation system; Rehabilitation; Unit costs; Urban centers; ACCNPQ::Engenharias::Engenharia Civil